ANALISIS TINDAK TUTUR KOMISIF DALAM SERIAL KOMEDI THE OFFICE - , Rusmiyati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Ministry of Forestry Republic of Indonesia through the Directorate General of Forest Protection and Nature Conservation (FPNC) cq Directorate PJLK2HL in collaboration with WWF Indonesia has established SNP REDD+ DAs as a pilot model for REDD+. It is intended to reduce carbon emissions in the area of peat swamp forest. Implementation of this program will involve the community arround the DAs location. For that we need a comprehensive note on: 1). Socio-economic conditions, 2). community perception, and 3). the relationship between socio-economic conditions and perceptions to formulate policy priorities in favor of the local community. This research used survey method. The research location are six hamlet, and two villages around the SNP REDD+ DAs site. Respondents were selected using purposive sampling technique. the people responden arround SNP REDD+ DAs are whose have received the socialization of REDD+. For determination of policy priorities, the experts are scientist and practitioners from the Ministry of Forestry and WWF Central Kalimantan. Collecting data using questionnaires . Socio-economic conditions in the analysis by descriptive analysis methods , Community perception is analyzed by the Crosstab method. The relationship between socio-economic conditions and perceptions were analyzed with Spearman Rank test and analysis for policy priorities using AHP ( Analytical Hierarchy Process ) . In this research found: 1). Socio-economic conditions of the community around the SNP REDD+ DAs are mostly in appropriate circumstances to carry out activities in SNP REDD+ DAs implementation plan